Identification of mosquitoes (Diptera: Culicidae) from Mexico State, Mexico using morphology and COI DNA barcoding - Garza Hernandez, Javier Alfonso (2020)
Mosquitoes are commonly identified to species level using morphological traits, but complementary methods for identification are often necessary when specimens are collected as immature stages, stored inadequately or when delineation of species complexes is problematic. DNA barcoding using the mitochondrial cytochrome c oxidase subunit 1 (COI) gene is one such tool used for the morphological identification of species. A comprehensive entomological survey of mosquito species in Mexico State identified by COI DNA barcoding and morphology is documented in this paper. Specimens were collected from all the physiographic provinces in Mexico State between 2017 and 2019. Overall, 2,218 specimens were collected from 157 localities representing both subfamilies Anophelinae and Culicinae. A species checklist that consists of 6 tribes, 10 genera, 20 subgenera, and 51 species, 35 of which are new records for Mexico State, is provided. Three hundred and forty-two COI sequences of 46 species were analysed. Mean intraspecific and interspecific distances ranged between 0% to 3.9% and from 1.2% to 25.3%, respectively. All species groups were supported by high bootstraps values in a Neighbour-Joining analysis and new COI sequences were generated for eight species: Aedes chionotum Zavortink, Ae. vargasi Schick, Ae. gabriel Schick, Ae. guerrero Berlin, Ae. ramirezi Vargas and Downs, Haemagogus mesodentatus Komp and Kumm, Culex restrictor Dyar and Knab, and Uranotaenia geometrica Theobald. This study provides a detailed inventory of the Culicidae from Mexico State and discusses the utility of DNA barcoding as a complementary tool for accurate mosquito species identification in Mexico.